Successful Conversion From Parenteral Paricalcitol to Pulse Oral Calcitriol for the Management of Secondary Hyperparathyroidism in Hemodialysis Patients - Kumar, Jennifer; Tran, Ngoc-Tram Gia; Schomberg, John; Streja, Elani; Kalantar-Zadeh, Kamyar; Pahl, Madeleine (Journal of renal nutrition, 2016)
The management of hyperparathyroidism in hemodialysis patients involves the administration of phosphate binders, vitamin D receptor activators, and calcimimetics. Intravenous paricalcitol has been preferred over oral calcitriol as it may cause less hypercalcemia and hyperphosphatemia. However, there is little data looking at the efficacy and tolerability of oral calcitriol in the calcimimetic era particularly in a real practice-based experience. The University of California, Irvine free-standing dialysis center converted from routine intravenous paricalcitol to oral calcitriol due to pharmacy purchasing preferences. We report the efficacy, safety, and cost of such a change. Ninety-three preconversion intravenous paricalcitol and 91 postconversion oral calcitriol. Conversion to in-center, pulse, oral calcitriol (0.25 mcg = 1 mcg paricalcitol) 3 times a week from intravenous paricalcitol. Additional dose adjustments were made by the nephrologists based on clinical indications. Five-month average serum calcium, phosphorous, and intact parathyroid hormone levels and cardiovascular events pretransition and posttransition. There were 93 patients on intravenous paricalcitol between April 2013 and August 2013, of which 74 converted to oral calcitriol and were included in the postconversion group evaluated between October 2013 and February 2014. An additional 17 new patients had initiated calcitriol such that 91 patients were on oral therapy in the postconversion period. Sevelamer use increased from 41 (44.1%) patients preconversion to 48 (52.7%) postconversion, whereas calcium acetate use significantly dropped from 62 (66.7%) to 46 (50.5%) (P = .026). Cinacalcet use dropped slightly from 37 (39.7%) patients preconversion to 35 (38.4%) postconversion. Average serum calcium, phosphorus, and intact parathyroid hormone levels remained unchanged after conversion. Percent of values within Kidney Disease Outcome Quality Initiative guidelines were similarly maintained. Estimated vitamin D cost savings were $564 per person/year. No increase in the incidence of cardiovascular events was observed. We conclude that in-center distributed pulse oral calcitriol may be an effective, safe, and economical treatment option for the management of hyperparathyroidism in hemodialysis patients.